Optimisation of farm income in carp culture - application of linear programming technique - Jeyaraman, R (Indian Journal of Fisheries, 2011)
Farmers are considered profit maximizers hence optimization of farm incomebecomes the utlimate objective. Rice farming is becoming less profitable andtherefore fish culture has attracted farmers in farm production diversification.Farmers need information on the optimal combination of the different farmingsub-sytems for adoption. This note describes application of Linear ProgrammingTechnique for optimization of income in integrated rice-fish-duckvegetablefarming system. Results of the study revealed that farm incomeincreased from Rs. 6,739 in pure rice crop farm to Rs. 16,484 in the integratedrice-fish-duck-vegetable farming system. Besides 90-100 mandaysof employmentwere generated additionally, farm business risk reduced by 17.46 % andfarm income was optimised and stabilised